2004
DOI: 10.1126/science.1090922
|View full text |Cite
|
Sign up to set email alerts
|

TGF-ß Signaling in Fibroblasts Modulates the Oncogenic Potential of Adjacent Epithelia

Abstract: Stromal cells can have a significant impact on the carcinogenic process in adjacent epithelia. The role of transforming growth factor-beta (TGF-beta) signaling in such epithelial-mesenchymal interactions was determined by conditional inactivation of the TGF-beta type II receptor gene in mouse fibroblasts (Tgfbr2fspKO). The loss of TGF-beta responsiveness in fibroblasts resulted in intraepithelial neoplasia in prostate and invasive squamous cell carcinoma of the forestomach, both associated with an increased ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,087
4
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,257 publications
(1,124 citation statements)
references
References 17 publications
23
1,087
4
10
Order By: Relevance
“…One of the key signaling molecules produced by cancer-associated fibroblasts is transforming growth factor-b (TGF-b): TGF-b activates fibroblasts to increase ECM formation (Keski-Oja et al, 1988) and promotes epithelial cell and fibroblast proliferation, depending upon the complement of growth factors present in the local microenvironment (Roberts et al, 1985). Collectively, these studies support a model of tumorigenesis in which TGF-b signaling creates a permissive stromal state for epithelial cancer initiation and progression (Bhowmick et al, 2004;Cheng et al, 2005).…”
Section: Incorporating the Tumor Microenvironmentmentioning
confidence: 95%
“…One of the key signaling molecules produced by cancer-associated fibroblasts is transforming growth factor-b (TGF-b): TGF-b activates fibroblasts to increase ECM formation (Keski-Oja et al, 1988) and promotes epithelial cell and fibroblast proliferation, depending upon the complement of growth factors present in the local microenvironment (Roberts et al, 1985). Collectively, these studies support a model of tumorigenesis in which TGF-b signaling creates a permissive stromal state for epithelial cancer initiation and progression (Bhowmick et al, 2004;Cheng et al, 2005).…”
Section: Incorporating the Tumor Microenvironmentmentioning
confidence: 95%
“…Notably, the authors found that the polyp epithelium of Lkb1 þ /À and Lkb1 lox Sm22-Cre mice showed deficient activation of the transforming growth factor-b (TGFb) pathway. As stromal TGFb signals are important for gastrointestinal tumor suppression, these results indicate that defective stromal TGFb production because of LKB1 deficiency could contribute to tumor formation in the epithelium (Bhowmick et al, 2004;Kim et al, 2006). Although these data indicating a 'landscaper' function for stromal LKB1 are very compelling, the final resolution of the relative roles of LKB1 signaling in the gastrointestinal stroma and epithelium will await generation of mice with specific deletion in the latter compartment.…”
Section: Benign and Malignant Tumorigenesismentioning
confidence: 98%
“…Ablation of TGF-β responsiveness in fibroblasts exacerbates neoplastic progression in several tissues, including prostate, stomach, and breast, [18,28,29]. Others have reported that stromal ablation of the tumour suppressor Pten during mammary carcinogenesis results in accelerated tumourigenesis, via Ets2 inactivation, suggesting multiple pathways by which fibroblasts can inhibit neoplastic growth [30,31].…”
Section: From Tumour Suppressors To Tumour Promotersmentioning
confidence: 99%